Well, the first thing you have done wrong is (x+2)^2 does not equal to (x+2)+(x+2), it's (x+2)*(x+2)

so x^2+(x+2)*(x+2)=290

x^2+x^2+4x+4=290

2x^2+4x+4=290

2x^2+4x-286=0

now, you can either solve this by the quadradic formula, or factoring

QF: x=[-4±√(16+2288)]/4

x=(-4±48)/4

x=11 or -13

-------------------------------------

on your work

if you did x^2 + (x +2) + (x + 2) = 290, it should be x^2+2x+4, how did you get 2x^2 + 4x + 4 = 290?

-------------------------------------

Check: plug in 11

121+169=290

169+121=290